Novel mutation in TENM3 gene in an Iranian patient with colobomatous microphthalmia - Sepideh Gholami Yarahmadi; Fatemeh Sarlaki; Saeid Morovvati (Clinical Case Reports, 2022)
Abstract This investigation revealed a homozygous c.5069‐1G>C variation in TENM3 gene although has not been reported for its pathogenicity and can be considered as a novel mutation. The present finding can be used for genetic diagnosis and detection of carriers in the family and other patients with similar disease manifestations.